EFEKTIVITAS PENERAPAN SISTEM MANAJEMEN PENGADUAN ONLINE INTERAKTIF (SIMPONI) DI KABUPATEN KUDUS PADA TAHUN 2021-2022 - Zahra, Naily Fairuz; Erowati, dewi -; Marlina, Neny - (Journal of Politic and Government Studies, 2024)
SIMPONI is a digital-based service to convey problems and appreciation to the Kudus Regency Government. This study aims to analyse the effectiveness of SIMPONI implementation and its influencing factors. The theory used is the theory of policy effectiveness of Riant Nugroho (2012) which consists of “five right”, namely the right policy, the right implementation, the right target, the right environment, and the right process. The method used is descriptive qualitative. The results showed that the implementation of SIMPONI was less effective. Of the five aspects of assessment, only two aspect were found to be effective, namely the right target and the right process. While other aspects are not effective. The right aspect of the policy has not been effective because the SIMPONI policy was presented without emergency problems. The right aspect of SIMPONI policy implementation has not been effective, indicated by data on the increase in users in 2021-2022, but in fact there are still many people who do not know SIMPONI. The right aspect of the environment has not been effective because the majority of users stated that SIMPONI still needs improvement. Even though the overall effectiveness of SIMPONI is less, SIMPONI still makes it easier for people to submit complaints to the government. The supporting factors of SIMPONI policy are the availability of human resources, facilities and infrastructure, and budget. Meanwhile, the inhibiting factors are the lack of widespread socialization and the lack of maximum maintenance of the SIMPONI application. To increase the effectiveness of the SIMPONI application, the Office of Communication and Information along with related institutions need to conduct socialization using various communication channels to reach all levels of society. Improvement and development of technical and non-technical applications are also needed so that SIMPONI can be effective, efficient, and relevant to the needs of the community